Local government policies on healthy food promotion and obesity prevention: results from a national Australian survey. (7th July 2022) - Riesenberg, Devorah; Blake, Miranda R.; Boelsen‐Robinson, Tara; Peeters, Anna; Cameron, Adrian J.
Abstract: Objective : Local governments (LGs) often own or manage sport and recreation facilities and can promote health in these settings by implementing healthy food policies. The primary aim of this study was to assess the policies, attitudes and practices of Australian LGs relating to obesity prevention and the provision of healthy food in this setting. Methods : In July 2020, all 539 Australian LGs were invited to complete a survey. We assessed LG priorities to obesity prevention, promoting healthy eating and public health as well as the presence of healthy food policies in sporting facilities. Results : 203 (38%) LGs completed the survey. Improving public health was a high priority, while obesity prevention and promoting healthy eating were a medium priority. 22% of LGs reported that the priority given to promoting healthy food had increased over the previous year and stayed the same at 65%. Ten per cent of LGs had a healthy food and drink policy in sporting facilities, with 32% reporting having made changes without a policy. LGs located in major cities, with larger populations and with more facilities reported having made more healthy changes at their facilities. Conclusion : Promoting health is a priority for LGs across Australia, but very few have policies relating to the food environments in their sporting facilities. Implications for public health : Ongoing monitoring is important to assess changes over time and identify LGs where greater support is required.